PENINGKATAN PROSES PENGERINGAN KERUPUK IKAN DI DESA TENGAH KECAMATAN PELAYANGAN KOTA JAMBI - Novarini Novarini; Sukadi Sukadi; Okka Raisa Lestari (Aptekmas Jurnal Pengabdian pada Masyarakat, 2019)
Tengah Village, District of Pelayangan, Jambi City is a potential area to develop fish cracker processing business. This area is close to the Batanghari River which is a producer of river fish such as cork fish. The main process in making crackers is the drying process. Improper drying process makes the crackers have poor quality. During this time, the drying process is still carried out by drying in direct sunlight which takes two days. In this condition, hygienic of the crackers are not guaranteed. It requires a simple and practical dryer to solve these problems. The dryer is made to have a greenhouse-like effect. The main ingredients of the drying wall (top and sides) are made of polycarbonate which is very good at absorbing heat from ultraviolet. The results of the practice of using this dryer in the Community Service program showed that the drying process only took 3 hours and the results of the crackers were cleaner, whiter, and more expanded..